2008
DOI: 10.1016/j.jvs.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Colon ischemia following abdominal aortic aneurysm repair in the era of endovascular abdominal aortic repair

Abstract: CI remains a serious complication following AAA repair. In the univariate analysis, EVAR was associated with a lower rate of colonic ischemia. However, the logistic regression analysis showed that only rupture, long duration of operation, and prior renal disease were independently associated with CI. Within the two treatment modalities, the mortality rate remained identical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 31 publications
5
105
1
5
Order By: Relevance
“…Female gender was associated with increased incidence of IC in two studies [9,10] . The natural logarithm of a disease severity score was recognised as positively associated with development of ischaemic colitis (mean severity score in IC 1311 vs 389 in no-IC, p<0.001) [9] .…”
Section: Patient Factorsmentioning
confidence: 94%
See 4 more Smart Citations
“…Female gender was associated with increased incidence of IC in two studies [9,10] . The natural logarithm of a disease severity score was recognised as positively associated with development of ischaemic colitis (mean severity score in IC 1311 vs 389 in no-IC, p<0.001) [9] .…”
Section: Patient Factorsmentioning
confidence: 94%
“…The reported rates of ischaemic colitis after elective surgery ranged from 0% to 4.6% [11,12] versus 5% to 20.5% [13,14] after emergency surgery. Six studies looked in more depth at emergency presentations and found those who had ruptured aneurysm demonstrated a higher rate of IC compared to those who had not ruptured (3.2 to 6.4 times more likely in ruptures) [9,13,15,10,16,17] . The studies reporting this are retrospective cohort studies.…”
Section: Pre-operative Factorsmentioning
confidence: 99%
See 3 more Smart Citations